INCREASING STUDENTS' ENGAGEMENT IN SPEAKING ENGLISH THROUGH STORYTELLING TECHNIQUE - Ilahi, Muhammad; Umam, Amalul; Prasetya, Eska (FKIP Universitas Ibn Khaldun, Bogor, 2024)
The ability to speak English is one of the main prerequisites for every student to be ready to compete in the era of globalization. Due to this quite urgent condition, of course educators have an important role and responsibility to find a solution. So that one day students will have sufficient provisions to compete globally, both in the world of education and the world of work they choose. One form of effort that educators can make to overcome students' problems in learning English is by innovating learning activities. Learning activities using storytelling techniques have been proven to be effective because they can increase student involvement in speaking English. Where during learning activities each student feels happy and has the opportunity to talk about things they have experienced. Plus there is a more comfortable space for students to express themselves through stories in small groups. Students who have more knowledge and skills can share suggestions and input with other students who are below them. Apart from that, good cooperation is created within it